Piagsugpatan stories of the Mandaya - Lee, Marcy Dans (Adarna House, Inc., 2013)
"For the Mandaya people, Piagsugpatan or the horizon is a part of their lives. Piagsugpatan bridges the three material worlds : Langit, Lupa, and Ugsuban."